Does brand authenticity alleviate the effect of brand scandals?. Issue 4 (July 2018) - Guèvremont, Amélie; Grohmann, Bianca
Abstract This research investigates to what extent brand authenticity lessens the impact of a brand scandal on consumer responses to the brand involved in the scandal. A 2 × 2 experiment shows that consumers responded more favourably to a more (vs. less) authentic brand in the event of a scandal. The protective effects of higher levels of brand authenticity emerged for emotional and behavioural brand outcomes (i.e. greater affection and willingness to pay) and brand-related inferences (i.e. lower perceived responsibility for the scandal and hypocrisy). Nonetheless, even a more authentic brand was harmed by a brand scandal (vs. no scandal). This suggests that higher levels of brand authenticity do not fully offset the negative consequences of brand scandals. A follow-up experiment ruled out that brand age drives these protective effects in case of a scandal. These findings give rise to theoretical and managerial implications.